RNA-seq Analysis of the Mechanisms Underlying Chalky Grain and Characterization of Two IAA Receptor Proteins OsAFB3 and OsAFB5 in Chalkiness Formation in Oryza sativa - Shaojie Shi; Huiying Wang; Wenjun Zha; An Huang; Ziyi Chen; Yan Wu; Junxiao Chen; Changyan Li; Bian Wu; Sanhe Li; Huashan Xu; Peide Li; et al. (Rice)
Abstract Grain chalkiness is an undesirable agronomic trait that negatively affects both the yield and quality of rice (Oryza sativa). The molecular mechanisms underlying chalky grain phenotype have remained largely unclear. In this study, we selected the rice variety HK300 with a high chalkiness, and ZR24D with a low chalkiness, as experimental materials and systematically characterized the reasons of grain chalkiness formation at molecular level by means of RNA-seq analysis. Analysis results revealed that the differentially expressed genes (DEGs) in these two rice varieties were significantly enriched in transcriptional regulation, sucrose and starch metabolism, and phytohormone signal transduction. Moreover, we found the expression of 13 genes related to trehalose pathway (4 out of 14 TPS genes and 9 out of 13 TPP genes in rice genome) were significantly different between the two varieties, indicating trehalose synthesis pathways may contribute to the increased chalkiness formation. Notably, the number of DEGs associated with the signal transduction pathway for indole-3-acetic acid (IAA), which has been rarely studied for its involvement in chalkiness formation, was the highest among those associated with plant hormone signal transduction. Among them, the expression of two IAA receptor genes, OsAFB3 and OsAFB5, were significantly lower in HK300 than that in ZR24D through RNA-seq and qRT-PCR. Furthermore, we newly validated the two genes negatively regulated the formation of chalkiness through gene knockout. Our findings provided the theoretical basis and novel gene resources for molecular breeding aimed at improving rice quality.